Biological Determinants of Health Disparities in Prostate Cancer - Martin, Damali N. (Curr Opin Oncol, 2013)
PURPOSE OF REVIEW: Prostate cancer mortality rates are highest among men of African ancestry in the United States and globally. Environmental exposures and ancestry-related factors may influence tumor biology and induce a more aggressive disease in this population. Here, we summarize the most recent advances in our understanding of race/ethnic differences in the tumor biology of prostate cancer with an emphasis on the excess disease burden among African-Americans. RECENT FINDINGS: Results from several DNA methylation studies showed an increased prevalence in DNA hypermethylation at disease-related loci in tumors from African-American patients compared with tumors from European-American patients. Analyses of genome-wide gene expression in prostate tumors revealed frequent alterations in the expression of genes related to immunobiology among the African-American patients, consistent with immune response differences between them and their European-American counterparts. Lastly, population differences in the frequency of oncogenic ETS-related gene rearrangements were evaluated in three studies which showed that these alterations manifest themselves most commonly in tumors from men of European ancestry, but are significantly less frequent in men of African ancestry, while least common in men of Asian ancestry. SUMMARY: Analysis of tumor markers indicates that tumor biological differences may exist between prostate cancer patients of African ancestry and those of European or Asian ancestry. These differences could affect disease aggressiveness and response to therapy.